Bryozoan Studies 2010 - Ernst, Andrej; Schäfer, Priska; Scholz, Joachim (Lecture Notes in Earth System Sciences,, 2013)
Bryozoa are a colonial animal phylum with a long evolutionary history, having existed from the early Ordovician (480 My) onward and still flourishing today. Several mass extinctions in earth history shaped and triggered bryozoan evolution through drastic turnover of faunas and new evolutionary lineages. Bryozoa are widespread across all latitudes from Equator to Polar Regions and occur in marine and freshwater environments. They are shaping benthic ecosystems and recording ambient environmental conditions in their skeletons. The book provides a synthesis of the current main topics of research in the field of Bryozoology including combined research on both extant, and extinct taxa. Fields or current research span molecular genetics and phylogeny, life history, reproduction and anatomy, biodiversity and evolutionary patterns in time and space, taxonomy, zoogeography, ecology, sediment interactions, and climate response.